Prolyl oligopeptidase is inhibited in relapsing-remitting multiple sclerosis - Tenorio-Laranga, Jofre (BioMed Central, 2010)
BACKGROUND: Multiple sclerosis (MS) is a complex, inflammatory and neurodegenerative disease of the central nervous system leading to long-term disability. Recent studies indicate a close association between inflammation and neurodegeneration in all lesions and disease stages of MS. Prolyl oligopeptidase (POP) is a proline-specific serine protease that cleaves several neuroactive peptides. This peptidase has been implicated in neurodegeneration, as well as in the modulation of the inflammatory response. METHODS: We examined plasma POP and the levels of an endogenous POP inhibitor from relapsing remitting MS patients and compared these with healthy controls, by monitoring the fluorescent changes due to standard fluorescently labelled substrate cleavage. We analysed the data in relationship to patient age and disease disability status. RESULTS: We observed a significant decrease in POP activity in plasma of relapsing remitting MS patients relative to healthy controls, coupled with an increase of POP endogenous inhibitor. The POP activity was also correlated with patient age and disability status. The lowered POP activity from plasma of MS patients could be rescued by reductants CONCLUSIONS: The decrease in circulating POP activity measured in MS is reverted by reductants. This suggests that POP inactivation in MS might be a result of the oxidative conditions prevailing in the plasma of the diseased patients. Plasma levels of POP activity as well as those of their endogenous inhibitor are suggested as biomarkers of inflammation and oxidative stress in MS.